Combined Effect of Competitive and Manufacturing Strategies on Export Performance of Small and Medium Enterprises in Malaysia (Global Journal of Management and Business Research, 2014)
It is generally accepted that business strategy has a significant influence on the success of many organizations However it has been rarely tested in the context of export operation and performance on SMEs Thus the objective of this research is to determine the combined effect of competitive strategy and manufacturing strategy on export performance of small and medium enterprises SMEs in Malaysia Quantitative survey method was employed and data were collected from 201 exporting SMEs through structured questionnaires The results from regression analysis found both competitive strategy and manufacturing strategy have significant and positive relationships to export performance Manufacturing strategy was also found to be a more significant contributor to export performance of SMEs These findings emphasize the importance of adopting both the competitive strategy and manufacturing strategy among the owner managers of SMEs to enhance their performance and be successful in the international markets
Keywords: Competitive strategy; manufacturing strategy; export performance; small and medium enterprises